Ligation of intersphincteric fistula tract – a retrospective, single centre, individual surgeons’ experience for the management of complex fistula in ano - Virji, Safna Naozer; Khan, Sadaf (Journal of the Pakistan Medical Association, 2024)
Objective: To identify early treatment outcomes among patients having undergone ligation of intersphincteric fistula tract for complex fistula-in-ano in a tertiary care setting. Method: The single-centre retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised data from January 2016 to January 2021 of adult complex fistula-in-ano patients who underwent ligation of intersphincteric fistula tract procedure. All surgeries were done by a single surgeon. Pre- and post-operative Wexner continence scores were measured, and various factors, including change in continence, complete wound healing, postoperative infection and recurrence, were assessed. Data was analysed using SPSS 23. Results: Of the 20 patients, 15(75%) were females and 5(25.0%) were males. The overall mean age was 38.4±13.8 years. The median duration of surgery was 65 minutes (interquartile range: 57-99 minutes). There were 2(10%) patients who showed a change in continence after surgery to flatus alone. Complete healing was noted in 11(55%) patients. Recurrence was noted in 8(40%) patients; trans-sphincteric fistula-in-ano in 2(10%) patients, and inter-sphincteric fistula in 6(30%). Body mass index had a significant association with the change in continence (p=0.028). Conclusion: There was a comparable risk of recurrence after ligation of intersphincteric fistula tract surgery, but among those without recurrence, the post-operative outcomes were optimal and no faecal incontinence was noted. Key Words: Rectal fistula, Recurrence, Faecal incontinence, Surgical wound infection.